HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS PEMBANTU UNGASAN: THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND STUNTING INCIDENTS IN TODDLERS AT THE UNGASAN SUPPORTING COMMUNITY HEALTH CENTER WORKING AREA - Shelly Suastini, Ni Komang; Ari Sukmandari, Ni Made; Prihandini, Claudia Wuri (Politeknik Insan Husada Surakarta, 2025)
Stunting is a growth failure due to Nutritional Insufficiency lasting from pregnancy until the age of 24 months which causes disruption of growth in children. The purpose of this study was to analyze the relationship of exclusive breastfeeding with the incidence of stunting in toddlers in the Working Area of the Ungasan Auxiliary Health Center. This study is an observational study using case control design. The sample in the case Group was 34 children with stunting and 34 children without stunting in the control group. This research instrument uses a questionnaire. Sampling technique in the case Group using non probability sampling method with total sampling technique and in the control group using simple random sampling technique. Analysis of data with chi-square test and statistical test odds ratio (OR). Exclusive breastfeeding in the group of non-exclusive breastfeeding cases as many as 20 toddlers (58.8%), in the control group of exclusive breastfeeding as many as 28 toddlers (82.4%). The incidence of stunting showed children with stunting as many as 34 toddlers (50%) and normal children as many as 34 (50.0%). The results of the chi-square test, namely P Value (0.000) ? (0.05), there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers. The value of OR 6.667 where OR > 1 means that toddlers who are not exclusively breastfed are a risk factor for stunting. There is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers in the working area of the Ungasan Health Center. Toddlers who are not exclusively breastfed have a 6.667 times higher risk of stunting than toddlers who are exclusively breastfed. The results of this study are expected health workers and posyandu cadres to continue to educate about the causes of stunting in order to achieve optimal nutritional health in toddlers